Finance Capital a study in the latest phase of capitalist development - Hilferding, Rudolf (London Routledge, 2006)
This is the first English translation of one of the classical works of Marxist economic theory. When Rudolf Hilferding?s Finance Capital was first published in 1919 it was acclaimed by reviewers as a continuation of Marx?s Capital, and it has a major influence upon subsequent Marxist thought, especially in the analysis of imperialism where it provided some of the fundamental ideas for the theories of Bukharin and Lenin.
Includes index
Keywords: Finance